A case of relapsed gAChR-positive autoimmune autonomic ganglionopathy treated by plasma exchange and mycophenolate mofetil - Zhijie Lu; Xiaojie Cao; Mingyu Wang; Fang Peng; Lin Chen; Zegang Yin; Baiyang Zheng; Jin Fan; Mingjie Zhang (Frontiers in Neurology)
Autoimmune autonomic ganglionopathy (AAG) is a rare and acquired immune-mediated disease that leads to wide autonomic failure, mainly characterized by orthostatic hypotension, gastrointestinal dysfunction, anhidrosis and poorly reactive pupils. This disorder is usually associated with autoantibodies to the ganglionic nicotinic acetylcholine receptor (gAChR-Ab). In this study, we describe a case of a gAChR-Ab-positive AAG patient with two therapeutic stages. The patient responded well after the first stage of methylprednisolone pulse therapy and subsequent low-dose prednisone. However, AAG relapsed after stopping oral prednisone. In the second stage, repeated methylprednisolone pulse therapy was less effective than before. Fortunately, multiple plasma exchange treatments improved the patient’s symptoms. In the end, low-dose oral prednisone and mycophenolate mofetil provided significant improvement in this patient during long-term follow-up. AAG is a relatively rare neuroimmunological disease with insidious onset and confused clinical features, while it responds well to the conventional immunotherapy, and some patients may require a long-term immunotherapy. Emphasizing the importance of early detection and treatment in clinical practice. Moreover, it should be noted that the reduction and withdrawal of immunosuppressants should be slow and cautious.